Claiming the international - Blaney, David L.; Tickner, Arlene B. , 1964- (Worlding beyond the West, 2013)
A host of voices has risen to challenge Western core dominance of the field of International Relations (IR), and yet, intellectual production about world politics continues to be highly skewed. This book is the third volume in a trilogy of titles that tries to put the international back into IR by showing how knowledge is actually produced around the world. Claiming the International examines the problem of difference in the study of international relations by examining the limits and possibilities of distinct forms of worlding and the global imaginaries they give rise to. International relations are not about a single global reality that is experienced and responded to in different ways. While one form of global order might be hegemonic in particular registers, the world does not conform to this single version. An emphasis on worlding brings to light the situatedness of knowledge and experience, and constitutes a call for re-connecting to their particular anchorings in myriad geocultural sites